32.7k views
3 votes
If f(1)= 4 and f(n) = -3f(n-1) then find the value of f(6)

User Benny Tjia
by
5.3k points

1 Answer

0 votes

Answer:

-972

Explanation:

if f(1)= 4 and f(n) = -3f(n-1) then find the value of f(6)

If f(1)= 4

f(2) = -3f(2-1)

f(2) = -3f(1)

f(2) = -3(4)

f(2) = -12

f(3) = -3f(3-1)

f(3) = -3f(2)

f(3) = -3(-12)

f(3) = 36

f(4) = -3f(4-1)

f(4) = -3f(3)

f(4) = -3(36)

f(4) = -108

f(5) = -3f(5-1)

f(5) = -3f(4)

f(5) = -3(-108)

f(5) = 324

f(6) = -3f(6-1)

f(6) = -3f(5)

f(6) = -3(324)

f(6) = -972

hence the sixth term of the sequence is -972

User ZelkiN
by
5.0k points